+0  
 
0
279
1
avatar
(2x+1)/3 + 7 = (3x-1)/4
Guest Jul 9, 2017
edited by Guest  Jul 9, 2017
 #1
avatar+7324 
+1

\(\frac{2x+1}{3}+7=\frac{3x-1}{4}\)                                      Multiply both sides of the equation by  4  .

 

\(4\,*\,(\frac{2x+1}{3}+7)=3x-1 \\~\\ \frac{4(2x+1)}{3}+28=3x-1\)                        Distribute the  4  .

 

\(\frac{8x+4}3+28=3x-1 \\~\\ 3\,*\,(\frac{8x+4}3+28)=3\,*\,(3x-1) \\~\\ 8x+4+84=9x-3\)          Multiply both sides of the equation by 3 and distribute.

 

\(8x+88=9x-3\)                                    Subtract  8x  from both sides of the equation.

 

\(88=x-3\)                                                Add  3  to both sides of the equation.

 

\(91=x\)

 

 

Notice that we could have multiplied both sides by  12  to begin with and this would get rid of both fractions in one step. smiley

hectictar  Jul 9, 2017

26 Online Users

avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.